Pemberdayaan Kader Posyandu tentang Penanggulangan Stunting pada Balita di Desa Mlese Kecamatan Ceper Kabupaten Klaten - Priyono, Putri Kusumawati (Universitas Muhammadiyah Klaten, 2022)
Stunting is a chronic nutritional problem that is a national development priority listed in the 2020-2024 RPJMN. Mlese Village is included in 100 priority cities/districts for stunting child intervention in Indonesia. The main focus in dealing with stunting is the First 1000 Days of Life (HPK) which is held at the Posyandu. Cadres who play an important role in driving posyandu are expected to have good knowledge and high motivation in stunting prevention efforts. The purpose of this activity is to empower health cadres to increase knowledge and motivation about stunting prevention. The target of this activity is cadres in Mlese Village with a total of 30 participants. Empowerment activities using the lecture method and followed by a question and answer session. The results of the activity show that 77.55% of cadres have good knowledge, and as many as 68.26% have a moderate level of motivation. It is hoped that the empowerment of health cadres can be carried out consistently and continuously so as to improve the performance of cadres in optimal posyandu services